Development of novel cationic microemulsion as parenteral adjuvant for influenza vaccine - Sakalanunt Lamaisakul; Angkana Tantituvanont; Vimolmas Lipipun; Garnpimol Ritthidej (Elsevier, 2020)
Squalene-based oil-in-water (O/W) emulsions have been used as effective and safe adjuvants in approved influenza vaccines. However, there are concerns regarding the safety and side effects of increasing risk of narcolepsy. In present study, novel O/W microemulsions (MEs) containing wheat germ oil, D-alpha tocopheryl polyethylene glycol 1000 succinate (TPGS) and Cremophor EL (CreEL) or Solutol HS15 were formulated with/without a cationic surfactant, cetyltrimethylammonium bromide (CTAB) and then sterilized by autoclaving. Their physical properties and biological efficacies were evaluated. The results demonstrated that autoclaving reduced the droplet size to ∼20 nm with narrow size distributions resulting in monodisperse systems with good stability up to 3 years. Hemolytic activity, viscosity, pH, and osmolality were appropriate for parenteral use. Bovine serum albumin (BSA), a model antigen, after mixing with MEs retained the protein integrity, assessed by SDS-PAGE and CD spectroscopy. Greater percentages of 28SC cell viability were observed from CreEL-based MEs. Uptake of FITC-BSA-MEs increased with the increasing concentration of CTAB confirmed by CLSM images. Furthermore, cationic CreEL-based MEs could induce Th1 cytokine synthesis with an increase in TNF-α and IL-12 levels and a decrease in IL-10 level. In vivo immunization study in mice of adjuvants admixed with influenza virus solution revealed that nonionic and selected cationic CreEL-MEs enhanced immune responses as measured by influenza-specific serum antibody titers and hemagglutination inhibition titers. Particularly, cationic CreEL-based ME showed better humoral and cellular immunity with higher IgG2a titer than nonionic CreEL-based ME and antigen alone. No differences in immune responses were observed between mice immunized with selected cationic CreEL-based ME and marketed adjuvant. In addition, the selected ME induced antigen-sparing while retained immune stimulating effects compared to antigen alone. No inflammatory change in muscle fiber structure was observed. Accordingly, the developed cationic CreEL-based ME had potential as novel adjuvant for parenteral influenza vaccine.